Implementasi Penjatuhan Pidana Bersyarat bagi Anak yang Berkonflik dengan Hukum dalam Putusan Nomor 84/Pid.Sus-Anak/2020/Pn Plg Ditinjau dari Sistem Peradilan Pidana Anak (International Forum of Researchers and Lecturers, 2025)
In implementing the enforcement of criminal acts by children who are in conflict with the law, Children's Criminal Justice System Act regulates that children should be kept as far as possible from the judicial process and punishment for deprivation of liberty. Therefore, there are many choices of forms of punishment in the SPPA Law, one of which is conditional punishment. This research aims to see whether conditional sentences for children in conflict with the law have been provided optimally. This research is normative research in which the data is processed using qualitative descriptive methods to answer the existing problem formulation. The results of this research found that the judge had not maximized the application of Law No. 11 of 2012 concerning the juvenile criminal justice system in decision number 84/pid.sus-anak/2020/pn plg. In decision number 84/pid.sus-anak/2020/pn plg, the judge did not impose a conditional sentence even though conditional punishment is one of the main crimes in the SPPA Law and the defendant meets the requirements to receive it.